2004
DOI: 10.1017/s0021859604004034
|View full text |Cite
|
Sign up to set email alerts
|

The potential of long-chain fatty alcohols and long-chain fatty acids as diet composition markers: development of methods for quantitative analysis and faecal recoveries of these compounds in sheep fed mixed diets

Abstract: SU MMARYPrevious investigations have shown that the long-chain fatty alcohols and long-chain fatty acids of plant waxes have potential as diet composition markers. This study was conducted to measure faecal recoveries of long-chain fatty alcohols (C 20 -C 30 ) and long-chain fatty acids (C 20 -C 32 ) in sheep fed mixed diets. Methodology for quantitative analysis of these compounds in feed and faeces is also presented. The method was an extension of the original n-alkane method of Mayes et al. (1986) in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 15 publications
10
65
1
Order By: Relevance
“…By contrast, LCOH concentrations in the diet components were much higher than their alkane concentrations. This has been reported previously (Ali et al, 2004;Bugalho et al, 2004;Ali et al, 2005). In general, the LCOH concentrations we report confirm earlier reports (Bugalho et al, 2004;Ali et al, 2005;Fraser et al, 2006) that the predominant LCOH of grass species are C26OH and C28OH.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…By contrast, LCOH concentrations in the diet components were much higher than their alkane concentrations. This has been reported previously (Ali et al, 2004;Bugalho et al, 2004;Ali et al, 2005). In general, the LCOH concentrations we report confirm earlier reports (Bugalho et al, 2004;Ali et al, 2005;Fraser et al, 2006) that the predominant LCOH of grass species are C26OH and C28OH.…”
Section: Discussionsupporting
confidence: 93%
“…The DM content of feed offered, feed refused and faeces was determined by forced-air oven drying at 708C for 48 h. Organic matter (OM) was determined as the weight lost upon ashing feeds and faeces at 5508C in a muffle furnace for 24 h. Alkanes and LCOH were extracted from samples using a direct saponification procedure followed by column chromatography (Ali et al, 2004;Dove and Mayes, 2006) and quantified by gas chromatography using a modification (Salt et al, 1992) of the method of Mayes et al (1986) for alkanes and for LCOH, the method of Ali et al (2004) except that LCOH were not derivatised prior to chromatography. Tetracosane (C24 alkane) and tetratriacontane (C34 alkane) were used as internal standards for alkanes and heptacosanol (C27OH) as the internal standard for LCOH.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…In this study, the most accurate estimates of diet composition for both species were obtained when using the mean faecal concentration for the total of animals within species. These results are consistent with those reported by previous studies for horses and cattle with alkanes (Ferreira et al, 2009a) and LCFA markers (Ferreira et al, 2010), and for small ruminants with LCOH markers (Ali et al, 2004;Dove and Charmley, 2008;Ferreira et al, 2012 and2015) and highlight the need of using accurate estimates of markers' FR to improve the accuracy of diet composition estimates in both horses and cattle.…”
Section: Diet Composition Estimatessupporting
confidence: 91%
“…For cattle, a positive association between CCL and LCOH FR was found. A similar trend was observed for horses and cattle when using LCFA (Ferreira et al, 2010) and alkanes (Ferreira et al, 2007 and2009a), and also in other ruminant species when studying LCOH (Ali et al, 2004;Dove and Charmley, 2008), LCFA (Ali et al, 2004;Ferreira et al, 2009b and and alkanes (Dove and Mayes, 2005;Ferreira et al, 2005 and2009a;Charmley and Dove, 2007). These data indicated that markers behave differently in the gastro-intestinal tract of ruminant and nonruminant species, and suggest that the disappearance of those with the shorter carbon-chain in the gut of ruminants occurs to a greater extent than in non-ruminants.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation